KONTROVERSI PERPANJANGAN MASA JABATAN KEPALA DESA 8 TAHUN 2 PERIODE PERSPEKTIF SOSIOLOGI HUKUM - Ardiyansyah, Rizky Ahadyan; Navis, Aulia Akbar; Rizal, Saiful (Universitas Muhammadiyah Ponorogo, 2024)
The term of office of the village head has been extended to 8 years (2 terms), with this provision it will trigger abuse of authority, considering that one of the aims of constitutional reform is to introduce limitations on executive power in order to create a balanced democracy in Indonesia. In this scientific study the author will analyze the impact of extending the term of office of the village head using a legal sociology approach. This research is packaged using normative research methods, the source of this research comes from primary materials in the form of relevant laws and regulations and books, while the sources of secondary material in this research are scientific papers in journals and other scientific articles and then correlating these problems with theory. sociology of law and statutory regulations. The results of the research show that the government policy regarding extending the term of office of village heads to 8 years and being able to be elected for 2 consecutive terms is a policy that is contrary to the concept of the rule of law, this is because the process taken by the government in forming this policy is considered to have political nuances. related to the situation of the 2024 presidential election, apart from that, the most fearful thing behind this policy is when this policy is used as a stepping stone by the government to extend the terms of office of other executives so that it is certain that the rule of law will be tainted by the government regime of this era. The conclusion is that the decision to extend the term of office of the village head is contrary to the aim of constitutional reform which seeks to limit executive power. What is most feared behind this decision is abuse of power by individual village heads due to holding power for too long accompanied by the absence of greater supervision intense.